Gene expression profiles of oral soft tissue‐derived fibroblast from healing wounds: correlation with clinical outcome, autophagy activation and fibrotic markers expression. (17th February 2021) - Rojas, Mariana Andrea; Ceccarelli, Simona; Gerini, Giulia; Vescarelli, Enrica; Marini, Lorenzo; Marchese, Cinzia; Pilloni, Andrea
Abstract: Aim: Our aim was to evaluate gene expression profiling of fibroblasts from human alveolar mucosa (M), buccal attached gingiva (G) and palatal (P) tissues during early wound healing, correlating it with clinical response. Materials and Methods: M, G and P biopsies were harvested from six patients at baseline and 24 hr after surgery. Clinical response was evaluated through Early wound Healing Score (EHS). Fibrotic markers expression and autophagy were assessed on fibroblasts isolated from those tissues by Western blot and qRT‐PCR. Fibroblasts from two patients were subjected to RT 2 profiler array, followed by network analysis of the differentially expressed genes. The expression of key genes was validated with qRT‐PCR on all patients. Results: At 24 hr after surgery, EHS was higher in P and G than in M. In line with our clinical results, no autophagy and myofibroblast differentiation were observed in G and P. We observed significant variations in mRNA expression of key genes: RAC1, SERPINE1 and TIMP1, involved in scar formation; CDH1, ITGA4 and ITGB5, contributing to myofibroblast differentiation; and IL6 and CXCL1, involved in inflammation. Conclusions: We identified some genes involved in periodontal soft tissue clinical outcome, providing novel insights into the molecular mechanisms of oral repair (ClinicalTrial.gov‐NCT04202822).